Routing and CDMA-MAC based cross-layering for wireless ad hoc networks. (2016) - Malwe, Shweta R.; Biswas, G.P.
Cross-layered technique performs better over centralised CDMA networks. This paper proposed a Routing-MAC cross-layer design for establishing source-destination route along with code assignment for CDMA-MAC implementation. Since the routing is dynamic, the proposed route and code-assignment results in efficient deployment of the network. Some improvements in terms of other parameters like code assignment complexity, code requirement, control overhead, etc. are also made. The pairwise code assignment (PCA) scheme is followed and three different approaches such as route-based, source-based and source-destination based PCA are proposed. A new wireless communication model comprising periodic mobility of nodes, dynamic formation of topology, routing and assignment of codes including data transmission as a cycle is proposed. The schemes are simulated on traditional and proposed network model, and improved performance regarding code-requirement and - confliction are achieved. Also the routing implemented on the proposed network model is found to be better than other wireless routing protocols.